Effects of HoMnO3 nanoparticles addition on microstructural, superconducting and dielectric properties of YBa2Cu3O7–δ - Bahboh, Abdalla; Shaari, Abdul Halim; Baqiah, Hussein; Chen, Soo Kien; Awang Kechik, Mohd Mustafa; Wahid, Mohd Haniff; Abd Shukor, Roslan; Talib, Zainal Abidin (Elsevier, 2019)
(YBa2Cu3O7–δ)1-x(HoMnO3)x (x = 0.0, 0.0025, 0.005, 0.01, 0.03 and 0.05) ceramics were fabricated by introducing co-precipitation synthesized HoMnO3 (HMO) nanoparticles during solid state reaction process of YBa2Cu3O7–δ (Y-123) superconductors. (Y-123)1-x(HMO)x samples were characterized using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) attached with energy Dispersive X-ray spectrometer (EDX), four-point probe measurement, AC susceptometer and impedance analyzer. Majority of XRD patterns were indexed to orthorhombic Y-123 phase. Besides, YBaMn2O5 (1.5–3.6%) and YBaMn2O6 (2.4–7.4%) phases were detected. FESEM images and EDX analysis showed the presence of agglomerated particulates related to Mn and Ho based phases residing in between the Y-123 grains. The superconducting behavior was significantly enhanced at x = 0.0025 while there was no major depression noticed in critical temperature (Tc-R=0) as the addition increased till x = 0.03 (Tc-R=0 = 88 K). AC susceptibility curves of composites samples manifested sharp transitions for samples with x = 0.0025 and 0.005. Dielectric parameters εr′ and εr′ʹ decreased as the frequency increased for all samples. The εr versus frequency measurements showed increment in εr′ and εr′ʹ values for all added samples as compared to Y-123 sample. The highest values for εr′ and εr′ʹ were obtained for sample x = 0.05 with the highest loss at lower frequency. The Nyquist plots of complex impedance were analyzed where two semi-arc circulars represent grain and grain boundary effect were deduced.